Urinary Tract Infection in Patients after Transurethral Resection of Bladder Tumor Procedure at a Tertiary Hospital - Kusnawan, Andi; Vijay Pramod, Sawkar; Safriadi, Ferry (Asian Pacific Journal of Cancer Care, 2023)
Background and objective: The incidence of urinary tract infection (UTI) in the early stages after transurethral resection of bladder tumor (TURBT) can lead to morbidity, prolonged hospital stays, increased patient costs, and pose a risk for bladder tumor recurrence. The global incidence of post-TURBT UTI varies between 2-39%. This study aimed to determine the incidence of UTI in patients after TURBT. Materials and Methods: This retrospective cross-sectional study utilized medical records from patients who underwent TURBT between 2017 and 2021 at a tertiary hospital. UTI after TURBT was defined by fever symptoms (≥ 38°C) and positive bacteriuria in urinalysis. Asymptomatic bacteriuria (ABU) was defined as positive bacteriuria without fever symptoms. Descriptive statistics were used to process the study results, which were presented in tables and explanatory narratives. Statistical analysis was conducted using SPSS version 26, with a p-value < 0.05 considered statistically significant. Results: A total of 140 patients underwent TURBT, and data from 92 patients were collected. Prior to TURBT, 56 (60.9%) patients tested positive for bacteriuria, but only 55 (59.8%) were asymptomatic. One patient (1.1%) had UTI before the TURBT and received antibiotic treatment prior to the procedure. After TURBT, urinalysis was performed on 9 (9.7%) patients. Among them, 4 (4.3%) patients experienced UTI, while 3 (3.3%) experienced ABU. The incidence of UTI after TURBT was found to increase the length of patient stays (p = 0.003). Conclusion: The incidence of post-TURBT UTI was determined to be 4.3%. Only 9.8% of patients underwent urinalysis after TURBT.